PENERAPAN ANALISIS BIPLOT UNTUK MENGGAMBARKAN LUAS PANEN KOMODITI JAGUNG DAN UBI KAYU DI KABUPATEN MANOKWARI TAHUN 2021 - Imelda Bobo Botunna; Indah Ratih Anggriyani (UNEJ e-Proceeding, 2022)
Biplot analysis is a method that is able to describe data in two-dimensional graphs. In the biplot analysis there are four important information obtained from the biplot display, namely the proximity between variables in an object, diversity of variables, correlation between variables and variable values ​​in an object. From the results obtained, the districts of East Manokwari, West Manokwari, South Manokwari, Warmare and Tanah Rubu have the same characteristics in that the value of harvested area is below the average in all corn and cassava commodity variables. October is the highest harvested area compared to other months. The harvested area for maize was found to be almost the same in all districts in May, as for cassava in June. There is a positive relationship in February and May for corn commodity. Meanwhile, for cassava, a positive relationship was found in February, March, April, November, June and September. The largest harvested area for corn commodity in 2021 is found in Prafi and Sidey Districts, while cassava is found in Prafi and North Manokwari Districts. The measure of the feasibility of the biplot produced by corn and cassava commodities, respectively, is 96.3% and 91.5%, which means that the information provided by the biplot of all the information contained in the data is good. Keywords: Biplot Analysis, Harvested Area, corn commodity, cassava commodity